Memórias de egressos das faculdades de direito de Pelotas/Brasil e Coimbra/Portugal (1960-1970): trajetórias no campo jurídico - Costa, Valesca Brasil (Universidade do Vale do Rio dos Sinos, 2014)
This research is dedicate for a study wich the objective is reconstruct, by memorialistic narratives, the trajectory of the graduates of two different School of Law: Pelotas/Brazil and Coimbra/Portugal. The time frame is the period between 1960 and 1970. The temporality is justified because comprises two totalitarian political regimes: the beginning of the Military Dictatorship in Brazil and the end of the Salazarism in Portugal. The investigation analyzes the condition of the graduates from these two institutions of Law education, figuring them as turncoats or heritor on the political contextualized scene. This study contributes for compose aspects of the history of the Law Institutions, especially on the local sphere, emphasizing commonalities and singularities in each of the colleges studied. The methodology used is based in the oral documents analysis, which they had as source memories from graduates of Law, and written documents. The theoretical framework is based, among other, in the Pierre Bourdieu concepts. It is important to say that the investigated institutions represents relevant meanings on the graduation of Lawyers context, as in Brazil both in Portugal. The analysis of documents permitted the perception of how much was the active participation of some students, graduates of the School of Law of Pelotas/Brazil and the School of Law of Coimbra, in the search for an end to the dictatorial regimes in force in the period, in both countries surveyed. The subjects, whose memoirs were produced, become the knowledge acquired in these higher education institutions, in some cases, an instrument in the struggle for justice and in others, the possibility of social mobility.
Keywords: Memória; História da educação; Herdeiros; Trânsfugas; Faculdade de Direito; Memory; History of education.; Heritors; Turncoats; School of Law; ACCNPQ::Ciências Humanas::Educação